2014
DOI: 10.4103/0970-9290.138339
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of two methods of ceramic inlay preparation by finite element

Abstract: Cements with minimum shrinkage and as thin layer as possible should be used. Filling the undercut with glass ionomer cement decreases the stress. Other experimental and clinical studies must follow this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…In Dentistry, the technique began to be studied in the 1970s 1 . The methodology has great versatility and analyzes the stresses produced in numerical models; it can be applied in research fields such as implantology 2 , orthodontics 3 , it can also simulate thermal 4 mechanical cycling 5 , water sorption 6 and polymerization shrinkage 7 and can also be applied in cavity optimization 8 and cusp bending 9 studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Dentistry, the technique began to be studied in the 1970s 1 . The methodology has great versatility and analyzes the stresses produced in numerical models; it can be applied in research fields such as implantology 2 , orthodontics 3 , it can also simulate thermal 4 mechanical cycling 5 , water sorption 6 and polymerization shrinkage 7 and can also be applied in cavity optimization 8 and cusp bending 9 studies.…”
Section: Introductionmentioning
confidence: 99%
“…2016 Jan-Feb; 45(1): 21-26 22 stress distribution in inaccessible areas 7 . It costs less than laboratory studies and it overcomes the ethical issues surrounding the use and collection of extracted teeth for research 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Stress concentrations at this thin ceramic margin have been associated with formation of microcracks in ceramic restorations. 30,31 This study found residual shrinkage stress concentrations in the margins of the ceramic restoration, which may add an additional challenge to this vulnerable area. Avoiding or reducing shrinkage stresses at the margins could therefore increase the longevity of ceramic restorations.…”
Section: Discussionmentioning
confidence: 80%
“…This may explain the relatively high percentage of postoperative sensitivity (13.3%) observed with dual cure conventional resin cement. 31 Although postoperative sensitivity tends to reduce with time, it is an undesirable incident. 35,36 Our study shows that delaying photo-activation may reduce shrinkage stresses at the pulpal floor and thus can reduce the incidence of postoperative sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…5,20,21 Yeni nesil adeziv uygulamalardaki teknolojik ilerlemelerle beraber güçlendirilmiş seramiklerin geliştirilme-siyle, inley restorasyonların yapımında da kullanımları artmıştır. 22 Seramik inleyler, diş yapısının korunması ve daha fazla koronal doku bırakılması açısından konservatif uygulamalardır ve indirekt posterior rezin kompozitlerden fiziksel anlamda daha üstündürler.…”
Section: -13unclassified